2015
DOI: 10.5433/1679-0359.2015v36n6p3595
|View full text |Cite
|
Sign up to set email alerts
|

AVG application regimes play an important role on pre-harvest drop and ripening of ‘Jonagold’ apples

Abstract: This study was carried out to investigate the effects of different AVG (aminoethoxyvinylglycine) treatments on pre-harvest fruit drop rates and ripening levels of 'Jonagold' apples. A total of 225 mg L -1 AVG dose was applied at once in a single application at different times or divided into doses and applied different times. Compared to control treatment, entire AVG treatments increased fruit removal force and significantly decreased the pre-harvest drop rates. AVG treatments applied at once (225 mg L -1 ) 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…In the 2015/2016 season, there was an interaction between the factors pre-harvest treatments and harvest date; however, regardless of the harvest date, any form of pre-harvest application of AVG caused a lower rate of ethylene production than the control. Likewise, Ozturk et al (2015) found a reduction in the ethylene production rate in 'Jonagold' apple sprayed with AVG in single and split rates of 225 mL -1 . AVG blocks the production of 1-aminocyclopropane-1-carboxylate (ACC), by inhibiting its synthase, reducing the production of ethylene in the fruit (Wendt et al, 2020).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…In the 2015/2016 season, there was an interaction between the factors pre-harvest treatments and harvest date; however, regardless of the harvest date, any form of pre-harvest application of AVG caused a lower rate of ethylene production than the control. Likewise, Ozturk et al (2015) found a reduction in the ethylene production rate in 'Jonagold' apple sprayed with AVG in single and split rates of 225 mL -1 . AVG blocks the production of 1-aminocyclopropane-1-carboxylate (ACC), by inhibiting its synthase, reducing the production of ethylene in the fruit (Wendt et al, 2020).…”
Section: Resultsmentioning
confidence: 88%
“…These results are in agreement with those of Ozkan et al (2012), who found a delay in the development of the red color in the epidermis of 'Braeburn' apples sprayed with a single rate of AVG. Ozturk et al (2015) reported that the application of AVG in a single rate resulted in a less intense red color in the epidermis of 'Jonagold' apple than split rates.…”
Section: Resultsmentioning
confidence: 99%
“…The physiological events regulated by ethylene, such as ethylene synthesis and therefore pre-harvest fruit drop, may be prevented by aminoethoxyvinylglycine (AVG) binding to the active site of enzyme 1-aminocyclopropane-1carboxylate synthase (ACS) and inhibiting theisis of ethylene immediate precursor aminocyclopropane-1carboxylate (ACC), which is thereafter converted into ethylene by ACC oxidase (ACO) (Huai et al, 2001). AVG, which inhibits the increase in internal ethylene, has been shown to be effective in preventing pre-harvest fruit drop (Byers, 1997;Kang et al, 2007;Dal Cin et al, 2008;Robinson et al, 2010;Yildiz et al, 2012;Ozturk et al, 2015;Aglar et al, 2016;Souza et al, 2019). In the study, smilarly with these results, AVG application had a positive effect on preserving the fruit retention force and thus preventing fruit drop, but this effect varied depending on the cultivar and application concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Since the abscission and maturation events occur simultaneously, the biochemical role of ethylene in abscission is unclear, it is known that the process following the initiation of abscission is accelerated by ethylene (Arseneault et al, 2016). Due to the effect of the auxin-ethylene interaction on the fruit drop, the effects of the bioregulators such as naphthalene acetic acid (NAA) that promotes auxin concentration (Yuan and Carbaugh, 2007;Dal Cin et al, 2008) and AVG that inhibits ethylene increase (Byers, 1997;Kang et al, 2007;Dal Cin et al, 2008;Yildiz et al, 2012;Ozturk et al, 2015;Aglar et al, 2016;Souza et al, 2019) on the pre-harvest fruit drop have been determined by previous studies. It has been reported that AVG is more effective than NAA in preventing pre-harvest fruit drop in apples (Greene et al, 1987, Yildiz et al, 2012.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that ethylene is the main signal molecule to induce fruit abscission in apple, oil palm and litchi [13][14][15]. Moreover, studies have shown that the fruit-setting rates can be improved by applying ethylene inhibitor AVG in apple [16]. In general, ethylene biosynthesis may be involved in the abscission process, and it plays an important role in the final stage of abscission.…”
Section: Introductionmentioning
confidence: 99%